State‐of‐the‐art imaging techniques in the management of preoperative staging and re‐staging of prostate cancer. (20th September 2018) - Schiavina, Riccardo; Chessa, Francesco; Borghesi, Marco; Gaudiano, Caterina; Bianchi, Lorenzo; Corcioni, Beniamino; Castellucci, Paolo; Ceci, Francesco; Ceravolo, Isabella; Barchetti, Giovanni; Del Monte, Maurizio; Campa, Riccardo; et al.
Abstract: We aimed to review the current state‐of‐the‐art imaging methods used for primary and secondary staging of prostate cancer, mainly focusing on multiparametric magnetic resonance imaging and positron‐emission tomography/computed tomography with new radiotracers. An expert panel of urologists, radiologists and nuclear medicine physicians with wide experience in prostate cancer led a PubMed/MEDLINE search for prospective, retrospective original research, systematic review, meta‐analyses and clinical guidelines for local and systemic staging of the primary tumor and recurrence disease after treatment. Despite magnetic resonance imaging having low sensitivity for microscopic extracapsular extension, it is now a mainstay of prostate cancer diagnosis and local staging, and is becoming a crucial tool in treatment planning. Cross‐sectional imaging for nodal staging, such as computed tomography and magnetic resonance imaging, is clinically useless even in high‐risk patients, but is still suggested by current clinical guidelines. Positron‐emission tomography/computed tomography with newer tracers has some advantage over conventional images, but is not cost‐effective. Bone scan and computed tomography are often useless in early biochemical relapse, when salvage treatments are potentially curative. New imaging modalities, such as prostate‐specific membrane antigen positron‐emission tomography/computed tomography and whole‐body magnetic resonance imaging, are showing promising results for early local and systemic detection. Newer imaging techniques, such as multiparametric magnetic resonance imaging, whole‐body magnetic resonance imaging and positron‐emission tomography/computed tomography with prostate‐specific membrane antigen, have the potential to fill the historical limitations of conventional imaging methods in some clinical situations of primary and secondary staging of prostate cancer.